Komunikasi Interpersonal di Dunia Virtual Remaja Pecandu Mobile Legends di Kelurahan Bojo Baru - Nur Ilham (Danudirja Setyabudi Nusantara, 2025)
Indonesia ranks first in Asia with 6.05 hours of mobile phone use per day, creating a paradox of high virtual connectivity but social isolation in the real world. This study analyses the transformation of interpersonal communication among Mobile Legends-addicted adolescents in Bojo Baru Village using the perspectives of Computer-Mediated Communication and Goffman's dramaturgy. A qualitative case study method was applied to seven informants (five adolescents aged 13-17 who played 8-15 hours/day, two supporting informants) through 200 hours of observation, in-depth interviews, and digital conversation analysis. Five phenomena were identified: (1)